(untitled) (Journal of Kathmandu Medical College, 2017)
Background: Urine collection in children especially in new born is a great challenge. A wide range of clinical interventions for urine collection is described in the literature, including non-invasive and invasive methods. Mid-stream urine collection is considered the most appropriate technique for older children. Here we are testing a method for obtaining mid- stream urine sample in newborns. Objective: To test a technique of urine collection for obtaining mid-stream urine sample in newborns. Method: A prospective feasibility study of a technique of urine sample collection based on bladder and lumbar stimulation maneuvers done in 100 newborns of less than 28 days of life over a period of one month. The main variable was the success rate in obtaining a midstream urine sample collection within four minutes and secondary variables were time required to obtain the sample and associated complications. Results: Mid- stream urine sample was collected successfully in 91% of babies. Mean time required for urine collection was 59.7 seconds with standard deviation of 46.4 seconds and median time was 47 seconds. No untoward complication other than controlled crying was seen. Conclusion: This is a quick and safe technique for mid-stream urine sample collection in newborn with high success rate and minimal discomfort. Journal of Kathmandu Medical College Vol. 5, No. 3, Issue 17, Jul.-Sep., 2016, Page: 82-84